The Relationship Between Smartphone Usage and Student Achievement at SMP 21 Pekanbaru - Hamidah Sari Batubara; Wahyuni, Rika Sri; Andriani, Andriani (PT Inovasi Pratama Internasional, 2024)
Morgan's research results (2015) in Indonesia, people aged 14-24 years who are dominated by 77% of students have and become the most active smartphone users compared to other ages. Smartphones have a certain impact on students. One of the impacts caused if used when learning activities are taking place is that it can lower students achievement. This study aims to determine the relationship of smartphone usage with student achievement in SMP Negeri 21 Pekanbaru 2019.Conducted in 25 february-28 february 2019 using primary and secondary data. This research is a quantitative analytic design with cross sectional approach with population of many as 770 people with a sample of 90 people using stratified proportionate random sampling technique. Processing data by using SPSS 17.0 then presented in tabular form. of research that from The results of the study revealed that the majority of smartphone use included in the medium category as many as 77.8% (70 people) and had good achievements much as 70.0% (63 people). Research shows that P Value ≥ α 0.388 ≥ 0.05, mean there is no relationship between smartphone usage with student achievement in SMP Negeri 21 pekanbaru 2019. This is due to the still high role of parents in paying attention to their children. Through this research, it is expected that educational institutions can use smartphones wisely so that they can improve learning achievement.